Gestational weight gain is a risk factor of stunting among children aged 6-23 months in Bangli District, Bali, Indonesia - Ni Putu Ayu Wulan Noviyanti; I Gusti Lanang Sidiartha; Anak Agung Sagung Sawitri; Kadek Tresna Adhi (Public Health and Preventive Medicine Archive, 2019)
Background and purpose: Stunting in children is a chronic nutritional concern that has short-term and long-term health effects. Several studies have shown inconsistent results related to the association between stunting and anemia and increased maternal weight during pregnancy. This study aims to determine anemia during pregnancy, increased body weight and weight gain during pregnancy based on body mass index (BMI) before pregnancy as the risk factors of stunting. Methods: A case control study was carried out using the baseline data of an intervention study conducted from April to September to prevent stunting in children aged 6-23 months in nine villages in Bangli District, Bali Province. Baseline data collection was conducted from December 2017–February 2018 by interviewing 330 mothers of the children and observation of their ANC records. The number of samples for the case control study was 156 children aged 6-23 months consisting of 78 cases and 78 controls (1:1). Cases were selected by systematic random sampling from 82 children with stunting and controls were selected in the same way from 248 children without stunting. Data analyzed were maternal age at pregnancy, education, employment, number of children, family income, height, hemoglobin level and maternal body weight during pregnancy. Multivariate analysis with logistic regression was conducted to determine the adjusted odds ratio (AOR) of each risk factor. Results: The increase in maternal weight during pregnancy which is not in accordance with maternal BMI before pregnancy and an increase in maternal weight of <10 or >12.5 kilograms are significantly associated with stunting with AOR=3.53 (95%CI: 1,55-8.07) and AOR=3.31 (95%CI: 1.24-8.85). Hemoglobin <11gr/dL during pregnancy was not found to be significantly associated with stunting (AOR=5.02; 95%CI: 0.80–31.71). Conclusion: The increase of maternal weight during pregnancy which is not suitable with BMI before pregnancy and an increase in maternal weight of <10 or >12.5 kilograms are risk factors for stunting in children aged 6-23 months. In addition to monitoring the increase of maternal weight during pregnancy, it is important to consider the mother’s BMI before pregnancy in order to reduce the risk of stunting.